Pengaruh Penggunaan Ekstrak Daun Teh Hijau (Camellia sinensis) pada Proses Pembuatan Naget Daging Sapi terhadap Sifat Kimia - Muhammad Fakhri Maulana; Lilis Suryaningsih; Andry Pratama (Jurnal Teknologi Hasil Peternakan, 2020)
Green tea is known as a plant who has many purpose as well as an antioxidant sources. The purpose of this research is to find out the effect of adding green tea (Camellia sinensis) extract in beef nuggets on chemical properties (moisture content, fat content, and polyphenol content). This research is an experimental research using completely randomized design method with 4 treatments and 5 repetition. The treatment that given was P1= beef nugget with no added green tea extract, P2= beef nugget + 0,5% green tea extract, P3= beef nugget + 1% green tea extract, and P4= beef nugget + 1,5% green tea extract with 5 repetition. Chemical analysis that used in this research is moisture content analysis, fat content, and polyphenols content. The obtained results then tested with anova, duncan, and polynomial test. The results showed that the treatment had a significantly real effect on polyphenols content but not on the moisture content and fat content. The addition of 1,5% green tea (Camellia sinensis) extract increase the polyphenol content of 305,96 mg/kg and influence 80,79% of the polyphenol content.